Successful management of health regions: Circumstances, challenges and competences in German health regions - Yvonne Behrens; Madlene Movia; Sandra Macher; Frank M. Amort (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2024)
Background: Health regions are associations of a wide variety of persons involved at regional level who are connected to the health sector. Along with different professions, these players represent a wide range of interests. Regional Health Network Managers manage the health regions in order to improve the health of the regional population (cf. Landesvereinigung für Gesundheit and Akademie für Sozialmedizin Niedersachsen 2018; Buck et al. 2019). The Erasmus+ project Com.HeNet surveyed the (inter-)national competences for regional health network management. Method: In order to identify the required competences for regional health network management, the project consortium conducted a comprehensive literature review. For this purpose, various scientific articles as well as grey literature were used. In addition, five interviews per country were conducted with experts in the field of health regions. The results were compiled and analysed for the required competences for regional health network management. Results: The study revealed that there is neither a uniform definition nor a uniform training for regional health network management in Germany. The experts recommend the inclusion of stakeholders from the fields of health, economy, politics, science and society in the network. Professional, scientific, practical and personal competences are necessary for the management of health regions. Conclusion: The management of health regions is an interdisciplinary field of work. In addition to professional competences, personal competences are also needed. The Com.HeNet project identified the competences for regional health network management.
Keywords: 360; Healthcare; Health Regions; Health Management; Health Education